2016
DOI: 10.1249/mss.0000000000000964
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diet versus Exercise on Metabolic Function and Gut Microbiota in Obese Rats

Abstract: Cardiometabolic impairments that begin early in life are particularly critical, as they often predict metabolic dysfunction into adulthood. Obesity, high-fat diet (HFD), and inactivity are all associated with adipose tissue (AT) inflammation and insulin resistance (IR), major predictors of metabolic dysfunction. Recent evidence also has associated the gut microbiome with cardiometabolic health. PURPOSE Compare equal energy deficits induced by exercise and caloric reduction on cardiometabolic disease risk para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
75
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 40 publications
10
75
1
3
Order By: Relevance
“…15,17 In this regard, a recent study from Welly and colleagues demonstrated that caloric restriction as a means to match the reduction in adiposity induced by VWR, led to similar effects on inflammatory gene expression when rats were fed a high fat diet. 16 The results from our current study support and add to these previous studies, as we observed that VWR attenuated the LPSmediated induction of TNF-a and MCP-1 mRNA expression in iWAT providing some evidence that the effects of VWR go beyond the attenuation of weight gain. Intriguingly, the effects of physical activity are The potential mechanistic basis for the protective effects of VWR against LPS induced adipose tissue inflammation are likely multifaceted.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…15,17 In this regard, a recent study from Welly and colleagues demonstrated that caloric restriction as a means to match the reduction in adiposity induced by VWR, led to similar effects on inflammatory gene expression when rats were fed a high fat diet. 16 The results from our current study support and add to these previous studies, as we observed that VWR attenuated the LPSmediated induction of TNF-a and MCP-1 mRNA expression in iWAT providing some evidence that the effects of VWR go beyond the attenuation of weight gain. Intriguingly, the effects of physical activity are The potential mechanistic basis for the protective effects of VWR against LPS induced adipose tissue inflammation are likely multifaceted.…”
Section: Discussionsupporting
confidence: 89%
“…Physical activity and exercise training increase indices of mitochondrial biogenesis in adipose tissue [9][10][11][12] and induce a thermogenic gene program that is characterized by increases in uncoupling protein 1 (UCP-1) mRNA expression and/or protein content in some 9,13,14 but not all studies. 15,16 While physical activity can protect against adipose tissue inflammation induced by obesity, 15,17 this beneficial anti-inflammatory effect is likely mediated, at least in part, through reducing the accretion of adipose tissue. 18 Thus, as the inflammatory cascade induced by sepsis manifests without significant changes in the accretion of adipose tissue, it is important to determine if physical activity or exercise protect against sepsis induced inflammation in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…89,90 In adult rodents, exercise changes the gut microbial populations. [140][141][142][143] In turn, the composition of the gut microbiota may influence exercise performance of mice through anti-oxidant enzyme production. 144 In mice, exercise attenuates gut dysbiosis due to exposure to polychlorinated biphenyls.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue is an active endocrine organ that is profoundly affected by exercise. Exercise lessens WAT inflammation and improves systemic metabolic health, even in settings of obesity (Vieira, et al 2009a; Welly, et al 2016a), although the mechanisms are not fully understood. Less is known about the effect of exercise on BAT inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about the effect of exercise on BAT inflammation. In this regard, we recently showed that exercise training also reduces obesity-induced BAT inflammation in rodents (Wainright, et al 2015; Welly et al 2016a). In addition, evidence suggests that exercise increases WAT mitochondrial content and function (Lee, et al 2014; Stallknecht, et al 1991; Stanford and Goodyear 2016; Wainright et al 2015), which is associated with metabolically healthier WAT.…”
Section: Introductionmentioning
confidence: 99%